The management of deep caries in UK primary care: A nationwide questionnaire‐based study. (9th July 2021) - Edwards, David; Bailey, Oliver; Stone, Simon; Duncan, Hal
Abstract: Aim: To investigate current approaches and attitudes towards the management of deep caries in primary dental care within the United Kingdom (UK). Methodology: Open distribution of an electronic questionnaire survey was undertaken to primary care dental professionals working in publicly funded National Health Service [NHS], privately funded, military and community dental services. Demographic variables investigated included the following: place of qualification, method of remuneration, level of restorative training, materials available, years qualified, appointment length and clinician type. Management variables focussed on case‐based scenarios. Univariate analyses of responses to questions were undertaken using χ 2 tests with sequential Bonferroni correction. Variables with a statistical relationship of p ≤ .2 were selected for binary logistic regression modelling. Results: A total of 657 responses were received. Practitioners with formal postgraduate qualifications (PGQ) were more likely (OR, 95%CI) to undertake further tests to aid diagnosis including: gaining a patient history (1.80, 1.01–3.20), periapical radiography (1.43, 1.01–2.03), cold pulp testing (2.079, 1.46–2.97) and electric pulp testing (1.65, 1.02–2.65). Rubber dam was infrequently used for deep caries management (29.2%). Non‐NHS practitioners were much more likely to use rubber dam (3.40, 2.15–5.37), as were those that had completed PGQ (2.24, 1.48–3.38). Non‐selective caries removal was used in deep caries by 41.4% of practitioners. Indirect pulp caps were carried out by 56.7% of practitioners. NHS practitioners were more likely to place calcium hydroxide (3.74, 1.97–7.15), whilst non‐NHS practitioners were more likely to place calcium silicate cements (CSCs) (3.303, 1.71–6.38) as were non‐UK graduates (5.63, 2.47–12.86) and those with PGQ (2.12, 1.17–3.87). Conclusions: This UK survey highlights significant variation in the management of deep caries. There is lack of consensus regarding the use of a standard systematic approach to diagnosing disease, with a reliance on history and tests with poor specificity. Non‐selective caries removal for managing deep carious lesions remains common, with low rubber dam compliance underlining a lack of asepsis. Notably, a significant number of practitioners placed indirect pulp caps, but CSCs and GIC were not commonly used. At present, although clear guidelines are available this is not translating into consistent management approaches in practice, suggesting that better dissemination of current treatments is essential to undergraduate and postgraduate groups.